2019
DOI: 10.1371/journal.pone.0226303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin administration on endocrine-metabolic parameters, visceral adiposity and cardiovascular risk factors in children with obesity and risk markers for metabolic syndrome: A pilot study

Abstract: BackgroundMetformin treatment (1000–2000 mg/day) over 6 months in pubertal children and/or adolescents with obesity and hyperinsulinism is associated with a reduction in body mass index (BMI) and the insulin resistance index (HOMA-IR). We aimed to ascertain if long-term treatment (24 months) with lower doses of metformin (850 mg/day) normalizes the endocrine-metabolic abnormalities, improves body composition, and reduces the carotid intima-media thickness (cIMT) in pre-puberal and early pubertal children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 50 publications
3
33
0
1
Order By: Relevance
“…The medical community has recognized overweight and obesity as an epidemic negatively affecting a large proportion of the pediatric population across the nation, introducing new physiological and social problems. Although most of the associated health concerns involve endocrine abnormalities and an increased risk of cardiovascular disease later in life [ 19 , 20 ], clinicians should also be aware of the orthopedic issues associated with childhood overweight, including an increased risk of fracture and greater fracture severity [ 21 23 ]. Growing numbers of reports are detailing higher rates of complications associated with surgical and conservative treatments in overweight children [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The medical community has recognized overweight and obesity as an epidemic negatively affecting a large proportion of the pediatric population across the nation, introducing new physiological and social problems. Although most of the associated health concerns involve endocrine abnormalities and an increased risk of cardiovascular disease later in life [ 19 , 20 ], clinicians should also be aware of the orthopedic issues associated with childhood overweight, including an increased risk of fracture and greater fracture severity [ 21 23 ]. Growing numbers of reports are detailing higher rates of complications associated with surgical and conservative treatments in overweight children [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…shows that 6 patients in the metformin group refused to continue, and 2 in the placebo group abandoned the study due to low attachment [50].…”
Section: Discussionmentioning
confidence: 99%
“…Most, although not all, clinical studies have shown that metformin, lowering IR, may reduce the risk of chronic vascular complications of diabetes and significantly decrease modifiable cardiovascular risk factors, including hyperglycemia and hyperglycemia -related inflammation and oxidative stress, increased platelet aggregation PAI, HbA1c, dyslipidemia, IR, visceral obesity, and blood pressure [ 192 , 193 , 194 ]. The effect of metformin on cardiovascular risk factors is depicted in Figure 2 .…”
Section: Clinical Aspects Of Metforminmentioning
confidence: 99%